Características da comunicação não-verbal entre o enfermeiro e o cego - Rebouças, Cristiana Brasil de Almeida (2005)
Study on the characteristics of non-verbal communication between the nurse and the blind patient, whose objectives are the following: analyzing the nurse’s non-verbal communication with the blind patient during the nursing attendance; testing the reliability index among the referees of non-verbal communication analysis; classifying the non-verbal signs, according to Hall’s referential (1986); verifying the association between the video recordings and the non-verbal communication factors; and identifying the barriers to non-verbal communication between the nurse and the blind patient. The approach adopted is exploratory, descriptive, and quantitative, aiming at gathering information for intervention and, therefore, for improvement in the quality of assistance to this clientele. The study has been developed during the period of February to April of 2005, in a reference healthcare unit, of secondary level, in the city of Fortaleza-Ce, with nurses that attended to diabetic patients, as diabetes may cause several ocular disorders, such as cataract and diabetic retinopathy. Previously, the fourteen nurses who attended to diabetic patients at the institution had been contacted. Of those, seven agreed in participating of the study, but only four made part of the study group. In what regards the selection of blind diabetic patients, it was performed at random, considering the ethical principles that govern studies with human beings. The group has been constituted, therefore, by people who went blind as a consequence of diabetes, and who were going to be attended by the nurses who were part of the study group. Five blind people integrated the study group. To the data collection, a video camera was employed, which recorded the entire nursing attendance between the nurse, the blind person and his/her companion. The instrument for data analysis to evaluate the non-verbal communication between the nurse and the blind person was elaborated according to Hall’s theoretical referential (1986), with emphasis on the proxemic theory, and received the designation Nurse - Blind Patient Non-Verbal Communication (CONVENCE). Simultaneously to the data analysis, CONVENCE was sent to three referees in order to be analyzed. To the analysis of the video recordings, three other referees were chosen, who agreed in participating in the study and that were trained according to the proposed referential. From CONVENCE, five categories were elaborated, with their respective sub-categories. Category 1: Spatial distance, with the sub-categories 1.1- distance, 1.2- posture, 1.3- axis, 1.4-contact. Category 2 – Social behavior, with the subcategories: 2.1-emblematic gestures, 2.2 illustrating gestures, 2.3 –regulating gestures. Category 3 – Facial behavior. Category 4 – Visual Code, with the subcategories: 4.1 – ocular opening, 4.2 looking direction. Category 5 – Voice volume. The training sessions and the data analysis were carried out with all the referees present in the same room and at the same time that had been preset in the beginning of the training. The video recordings were analyzed each fifteen seconds, summing up 1.131 non-verbal communication analyses. When analyzing the categories and subcategories, the main results that were observed are the following: In category 1, the subcategory minimal distance prevailed with 1.030 (91%), due to the fact that the environment were the attendance took place favored the adoption of almost exclusively that distance, either by the professional or by the patient. In this category, the subcategory 2 has shown that the sitting posture (98.3 %) almost obtained unanimity in the images that were analyzed. When addresser and addressee maintain the same posture, it means that they are attuned, sharing the same rhythm, degree of interest, and movement. Also, in this category, the subcategory 4, denominated contact, demonstrated that in 943 (83.3 %) interactions there was no contact. The most observed gesture in the subcategory ‘emblematic gestures’ was the moving of hands (762 or 67.4%). The looking direction, subcategory 4.2, deviated from the interlocutor added up 597 (52.8%) and centered in the interlocutor, 502 (44.4%). In all the video recordings, there were considerable interferences in the moment of the interaction nurse-patient. Such fact was considered a hindrance to communication. The nurse has to demonstrate interest during the interaction, and it is the look towards the patient that will favor this attention during the nursing attendance. It can be concluded, according to the data, that the nurse needs to know and to intensify the studies in non-verbal communication, and to adequate its use to the kind of patient being attended.